Late Holocene paleoenvironmental records in Eastern Bangladesh from lake sediments: A multi-proxy approach. (30th August 2020) - Garnier, J.-M.; Garnier, J.; Debnath, P.; Prado, L.F.; Yokoyama, E.; Das, R.K.; Mathé, P.-E.; Islam, M.S.
Abstract: Lacustrine sediments in a poorly documented region regarding to lake sedimentation and paleo-environments (Bangladesh) were investigated using a multiproxy approach. Pukurpara Lake is located in eastern Bangladesh at an elevation of 360 m above sea level with a maximum water depth of 28 m. An age-depth model allowed us to investigate the changes in sedimentation that occurred since 850 CE. The high resolution multielement analyses by micro-X fluorescence scanning (μXRF) showed multiple variations over short increments. Variation in the abundance of elements with depth as well the ratios of the abundance of some elements (Fe/Ti and Zr/Rb) suggested both rapid and long-term changes in the origin of the material deposited, which, in turn, suggested changes in weather conditions. Principal Components Analysis (PCAs) mixing μXRF and Magnetic Susceptibility data allow identifying changes in geochemical redox processes between the Medieval Warm Period (MWP) and Little Ice Age (LIA). The drastic changes in the different proxies (magnetic susceptibility, diatom assemblages, fresh water/marine water diatom ratios, abundance of Fe and S, and the Fe/Ti ratio) were interpreted to be the result of climate change before and after the MWP-LIA transition period, the Little Ice Age period being relatively wet.